Unsustainable oil : facts, counterfacts and fictions - Gordon, Jon, 1979- (The University of Alberta Press, 2015)
"Bitumen extraction is the lifeblood of Alberta, and there are many stories about the boom-and-bust economy. But what does literature have to say about the "progress" of petroculture? Jon Gordon maps out a new field of study by examining the relationship between culture and energy extraction, moving towards nuance and away from the entrenched rhetorical positions that currently dominate discussion. His examination of theoretical, political, and environmental issues in this groundbreaking book contribute to our understanding of the culture and the ethics of energy production within the Canadian context. Unsustainable Oil offers readers a chance to consider literature's potential in confronting the hegemony of the oil and gas industry, and will be particularly well-received by scholars and students of Cultural Studies, Literature, Ecocriticism, Energy Humanities, and Indigenous Studies."--